Analysis of phenotypic stability in 25 cowpea genotypes across six environments - Ngalamu, T.; Meseka, S.; Ifie, B.E.; Ofori, K.; Eleblu, J.S.Y. (2019)
Twenty-five cowpea (Vigna unguiculata L) genotypes were evaluated across six contrasting environments for phenotypic yield stability. Combined analysis of variance revealed significant differences among the genotypes and the main effects. A1B×D, BC×M, L1B×M, A1B×M, and BA×I were the best performing and stable genotypes. The non-parametric analysis showed that genotype IT93K-503-1 had the highest yield and BC×D had the lowest yield. Shukla stability analysis revealed Beledi A and Dan lla as the most stable across test environments and genotypes A1B×D, BC×M and BA×I were good performers. The coefficient of variability graphical approach showed that genotypes BC×I, A1B×M, A1B×D, Dan lla, TA×M, Mouride, L1B×I, BC×M and L1B×D were high yielding. This implies they would do well across the testing sites. However, genotype IT93K-503-1 should be promoted for cultivation in drought-prone environments.